Application of water quality index and multivariate statistical techniques for assessment of water quality around Yamuna River in Agra Region, Uttar Pradesh, India - Runit Isaac; Shaziya Siddiqui (Water Supply, 2022)
In this research, water quality index and multivariate statistical techniques were carried out on 14 water quality parameters collected quarterly (four times/year) from nine water sources in Agra, Uttar Pradesh, India, for one year (May 2019–April 2020). The water quality parameters included are the concentration of hydrogen ions (pH), Electrical Conductivity, Turbidity, Total Dissolved Solids (TDS), Total Hardness, Total Alkalinity, Calcium, Sulphate, Chloride, Magnesium, Iron, COD, DO, and BOD. The water samples collected show that the mean values of physicochemical parameters are in the range set by WHO and BIS except for hardness in summer (1,680 mg/L), monsoon (832.22 mg/L), winter (1,876.66 mg/L), spring (1,535.55 mg/L); TDS in summer (1,000.33 mg/L), monsoon (683.44 mg/L), winter (1,087.66 mg/L), spring (776.66 mg/L); and sulphate in summer (927.22 mg/L), monsoon (446.77 mg/L), winter (925.77 mg/L), spring (944.88 mg/L), which indicate bad quality of water. The WQI values were calculated for three locations in different weather conditions. WQI values in summer, winter and spring are 630.90, 279.61, 279.91, showing that the river water is not suitable for drinking purposes whereas the WQI value in monsoon is 75.89, showing that water is fit for drinking purposes due to the dilution of the river water. A moderate positive correlation was observed for turbidity with total hardness, iron, total alkalinity, and sulphate. Negative correlation was observed with pH. Moderate correlation was seen with TDS–EC (0.608), TDS–Alkalinity (0.7794), EC–Ca (0.723), and strong correlation was observed for BOD–DO (0.941) and Ca–Mg (0.999). Principal component analysis revealed that five factors were significant (eigenvalue > 0.5) with total variance of 39.43%–85.19% respectively. The ICP-MS study of water samples from point sources indicate the presence of Ni2+, Cr6+, Co2+, Mn2+, Cu2+, and Zn2+ ions at higher concentrations. HIGHLIGHTS WQI values in summer, winter and spring are 630.90, 279.61, 279.91, showing that the river water is not suitable for drinking purposes.; WQI value in monsoon is 75.89, showing that water is fit for drinking purposes due to the dilution of the river water.; ICP-MS detects the presence of metal ions such as Ni2+, Cr6+, Co2+, Mn2+, Cu2+, Zn2+.; Multivariate statistical analysis reveals that five parameters are responsible for the high values of WQI.;